Effects of Using Multifaceted Strategic Method on Practices of Registered Nurse in Blood Culture Collection and Blood Culture Contamination Rate - thammathat, narisara (Health Science Clinical Research, 2023)
ABSTRACT Objective : To study the effects of using the multifaceted strategic method on the knowledge and practice of registered nurses in blood culture collection and compare blood culture contamination rate in blood culture before and after using the multifaceted strategic method. Methods : In this quasi-experimental research, one group pre-test and post-test design study aimed to develop a program to promote strategies in implementing evidence-based practices in management of blood culture collection among nurses. The samples were 44 registered nurses working in the Stroke Unit, Medical intensive care unit, and Respiratory intensive care unit in Uttaradit hospital, and sampling all the blood cultures from the 106 samples. The multifaceted strategic method consisted of the appointment of the lead team, knowledge training, demonstration by video, a reminder poster, performance feedback, and device support. The research instruments included a blood culture recording form, a questionnaire for the knowledge test, and competencies test in blood culture techniques. The results of the content validity index were .95 and reliability were 0.80 and 0.81 respectively. Analyzed by frequency, percentage, mean, standard deviation, fisher exact probability test, and paired sample t-test. Results : 1) After using the multifaceted strategic method to promote blood culture collection practice, the registered nurses, average knowledge score was increased from 8.2 to 10.4 and statistical significance at p <0.001. 2) After using the multifaceted strategic method to promote blood culture collection practice, the average competencies score was increased from 34.3 to 35.9, and statistical significance at .01. 3) After receiving the multifaceted strategic method to promote blood culture collection practice, the contamination rate was lower from 6.2% to 2.8%. Although the blood culture contamination rate is not statistical significance, the risk of blood contamination reduces to 54.7 % Conclusions: Using multifaceted strategic method had effects on registered nurses’ higher knowledge and practice in blood culture collection and reduced blood culture contamination rates lower than 3.0% Keywords: Multifaceted Strategic Method, Blood Culture Contamination Rate, Blood Culture Collection